The Impact of Structural Policies on Trade-Related Adjustment and the Shift to Services - Kongsrud, Per Mathis (OECD Economics Department Working Papers, 2005)
What policy reforms are most urgently needed to remove obstacles to output and employment growth in service sectors and to enhance economies' ability to adjust to structural change as a result of changing trade patterns? This paper reviews the impact of the structural policy framework conditions on the development of the service sector and economies' adjustment capacities. The paper builds on and summarises a vast body of previous work and briefly reviews policy recommendations given to countries in various surveillance processes in the OECD.